Genetic Markers of Cardiovascular Disease in Rheumatoid Arthritis - Luis Rodríguez-Rodríguez; Raquel López-Mejías; Mercedes García-Bermúdez; Carlos González-Juanatey; Miguel A. González-Gay; Javier Martín (Hindawi Limited, 2012)
Cardiovascular (CV) disease is the most common cause of premature mortality in patients with rheumatoid arthritis (RA). It is the result of an accelerated atherosclerotic process. Both RA and atherosclerosis are complex polygenic diseases. Besides traditional CV risk factors and chronic inflammation, a number of studies have confirmed the role of genetic factors in the development of the atherogenesis observed in RA. In this regard, besides a strong association between the HLA-DRB1*04 shared epitope alleles and both endothelial dysfunction, an early step in the atherosclerotic process, and clinically evident CV disease, other polymorphisms belonging to genes implicated in inflammatory and metabolic pathways, located inside and outside the HLA region, such as the 308 variant (G>A, rs1800629) of the TNFA locus, the rs1801131 polymorphism (A>C; position + 1298) of the MTHFR locus, or a deletion of 32 base pairs on the CCR5 gene, seem to be associated with the risk of CV disease in patients with RA. Despite considerable effort to decipher the genetic basis of CV disease in RA, further studies are required to better establish the genetic influence in the increased risk of CV events observed in patients with RA.